Public policy and the ‘sustainability’ of adult education - Milana, Marcella; Rasmussen, Palle; Holford, John (Alma Mater Studiorum - Università di Bologna, 2014)
Sustainable growth and development are intrinsically linked with the ways societal problems are thought of and addressed in public and private policy. However, at times when social and economic crises have shown the fragility of existing institutions and policies, it is important to debate how sustainability is – and could be – integrated into educational policy studies. We therefore begin by summarising the conditions under which the concept entered political debate and how it has influenced educational research. We then argue for a rethinking of its ontology: this, we suggest, can shed new light on its relationships with adult education policy and social justice.